Monitoring Implementation Impact of the EU-Indonesia’s VPA on SME Livelihood - Rahmanta Setiahadi; S. R. Kartika Sari; Ahmad Maryudi; Julia Kalmirah; Liliana Baskorowati (International Journal of Forestry Research)
The Europe Union (E.U.) has agreed to grant the Forest Law Enforcement, Governance and Trade (FLEGT) license to Indonesia as the first country in the world to receive it. FLEGT VPA (Voluntary Partnership Agreement) is a bilateral agreement between the European Union (E.U.) and wood exporting countries, to improve forest governance sector and ensure that timber and wood products imported into the E.U. are produced by the laws and regulation of partner countries. The Indonesian government has obliged to implement Article 12 relating to social safeguards. Indonesia has to periodically monitor to see the extent to which the VPA has an environmental and social impact that affect the lives and welfare of vulnerable and marginalised groups. The purpose of this study is to analyse how the effect of implementation of the Sistem Verifikasi Legalitas Kayu (SVLK) as part of VPA in the small and medium forestry industry sector. Methodology survey with focus group discussions, structured interviews, and semistructured interviews to find out the response and opinion of SME’s owner and employee addressed the effect of SVLK in East Java and Central Java, Indonesia. The theory of change (ToC) was used to consider the implications of SVLK implementation on the sustainable livelihood of small and medium enterprises (SME’s). The results of this study showed that SVLK had a more significant impact on livelihoods, as follows. First, the vulnerable and marginalised groups need to be supported by stakeholders to encourage readiness in faces of SVLK impact. Second, SVLK is susceptible to the effects and at risk of losing livelihoods for women and disabled groups in a short time. This group includes vulnerable groups of aspects of adaptability and sensitivity to the effect. Third, SME’s worker groups who do not have a labour organisation are sensitive to the impact on the workplace company. This group is classified as a group that is quite vulnerable if the effect lasts long enough and on a large scale of impact.